2005
DOI: 10.1002/14651858.cd003566.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cardioselective beta-blockers for chronic obstructive pulmonary disease

Abstract: A report by the Australian Institute of Health and Welfare (AIHW) shows that drugs and some interventions for cardiovascular disease are underused in rural areas. 1 It found that rural patients are getting far fewer prescriptions for beta blockers, ACE inhibitors, statins and warfarin than other Australians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
177
2
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(202 citation statements)
references
References 103 publications
3
177
2
18
Order By: Relevance
“…Often less effective alternatives such as calcium channel blockers are employed as anti-anginals in their place [29]. It has become apparent that cardioselective b-blockers such as atenolol and bisoprolol are safe in COPD [30]. Such agents should not, therefore, be withheld from COPD patients if there is an appropriate indication [31].…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…Often less effective alternatives such as calcium channel blockers are employed as anti-anginals in their place [29]. It has become apparent that cardioselective b-blockers such as atenolol and bisoprolol are safe in COPD [30]. Such agents should not, therefore, be withheld from COPD patients if there is an appropriate indication [31].…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…[13][14][15][16][17] Finally, epidemiological studies and meta-analyses clearly demonstrated in non-selected COPD populations (with or without heart diseases) that BB treatment decreased mortality and acute exacerbations of COPD. [1][2][3][17][18][19][20] The possible mechanisms of the beneficial effects (cardioprotection mainly) of BB in the setting of COPD include: the presence of subclinical heart disease (ischemic heart disease, heart failure, arrhythmias etc. ), 5 the presence of clinically manifest heart disease, 10 the attenuation of cardiovascular side effects of beta-agonist medication, 11 and the correction of bronchial beta2-receptor down-regulation induced by beta-agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one of the observations regarding BB treatment was its -seemingly paradoxical -beneficial effect in case of chronic obstructive pulmonary disease (COPD). [1][2][3] This may imply changing the current paradigm, which consists in a relative contraindication of BB in COPD, due to the fact that they may cause bronchospasm.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of RCTs studying effects of ß1-selective blockers on lung function (FEV 1) and respiratory symptoms in people with COPD using ß2-agonists identified 11 single dose and 11 repeated dose trials [41]. Administration of single doses of ß1-selective blockers to 131 patients was not associated with a change in FEV1 compared to placebo or to baseline controls, (mean difference (MD) -2.08%, 95% CI -5.25 to 1.09), in absolute terms the MD was 33ml of FEV1.…”
Section: 1mentioning
confidence: 99%